A Content Incontinent: Report of Liposomal Bupivacaine Induced Fecal Incontinence. (22nd September 2016) - Shapera, Emanuel A.; Rai, Vinay K.
Abstract : Proper surgical management of anal fistula demands sound clinical judgment and extraordinary care to prevent incontinence and adequate postoperative pain control and provide satisfactory resolution to optimize quality of life. Fecal incontinence can be a devastating complication of procedures performed for fistula in ano . We report a unique case in which temporary incontinence (for less than 4 days) followed injection of liposomal bupivacaine for postoperative pain control after draining seton placement for fistula in ano . Patients and physicians should be aware as it may be mistaken for a more serious anatomical and permanent cause of fecal incontinence.